Evaluation of anion exchange resin for sorption of selenium (IV) from aqueous solutions - A. El-Tantawy; E. M. Abu Elgoud; S. E. A. Sharaf El-Deen (BMC Chemistry)
Abstract In this work, selenium (IV) ions were adsorbed from aqueous solutions by the strongly basic anion exchange resin Amberlite IRA-400. The morphology of the resin before and after Se(IV) sorption was investigated using different techniques such as energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). To determine the ideal sorption conditions, a batch approach was used to examine the variables affecting Se(IV) sorption performance, including pH, shaking time, adsorbent dosage, initial metal ion concentration, and temperature. The results showed the optimal parameters for the highest percentage of selenium (80.25%) at an initial concentration of 100.0 mg L−1, pH 3.0, the adsorbent dosage of 10.0 mg, and the shaking time of 60.0 min. According to the experimental findings, the sorption process was satisfactorily explained by the pseudo-second-order kinetic model. The maximum adsorption capacity at pH 3.0 was 18.52 mg g−1, and the adsorption rather well followed the Langmuir adsorption isotherm. Moreover, exothermic and spontaneous sorption reaction was the result of thermodynamic properties (negativity of both ΔG° and ΔH°). The adsorption phase's random distribution of the resin-solution interface is indicated by the positive value of ΔSo. Finally, the desorption study was performed using different concentrations of desorbing agents; HNO3, HCl, and sodium acetate. The results illustrated that the effective desorbing agent was 1.0 mol L-1 HNO3, with desorption efficiency reaching about 96.4%. Finally, the Amberlite IRA-400 demonstrated excellent adsorption–desorption behavior over five times, suggesting that the Amberlite IRA-400 could be an effective candidate for the sorption of Se(IV) from several metal ions that occur in fission products.